Microstructure and Thermal Analysis of Brake Pads Developed from Asbestos-Free Materials - Abutu, J.; Lawal, S. A.; Lafia-Araga, R. A.; Ndaliman, M. B.; Oluleye, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
This study was conducted on developed asbestos-free brake pad using coconut shell and seashell as fillers. The use of hazardous reinforcement like asbestos fiber in friction materials is being avoided because of its carcinogenic effects. Rule of mixture technique was utilized during sample formulation and a weight percent of 52% filler material, 5% friction modifier, 8% abrasive and 35% binder were utilized for production. A multi-response optimization technique (grey relational analysis) was used to obtain an optimal process parameter of moulding pressure (14 MPa), moulding temperature (140 ºC), curing time (8 minutes) and heat treatment time (5 hours) for coconut shell-filled brake pad and moulding pressure (14 MPa), moulding temperature (160 ºC), curing time (12 minutes) and heat treatment time (1 hour) for seashell-filled brake pad. Thermal analysis of commercial and optimized samples shows that the commercial brake pads possesses a better thermal stability compared to the optimized formulated brake pad samples with the coconut shell-filled samples showing the least thermal resistance. Also, microstructure analysis of the impact fractured surfaces of the commercial, seashell and coconut shell-filled brake pad was conducted using scanning electron microscope (SEM). The results revealed that compare the commercial and seashell-filled samples, there were more uniform distribution of the resin in the coconut shell-filled composite leading to an improved bonding and closer inter- packing distance between its constituent particles and the epoxy resin. It was also revealed that the commercial brake pad possessed a higher thermal stability as the components were not noticeably degraded at temperatures at which the coconut shell and the seashell filled brake pads showed appreciable degradation.